DIGITAL REPRESENTATION OF CULTURAL HERITAGE THROUGH GENERATIVE AI: APPROACHES AND EVALUATIONS IN VISUAL COMMUNICATION DESIGN - Banu Erşanlı Taş (PEOPLE: International Journal of Social Sciences, 2025)
This study examines the impact of generative artificial intelligence technologies on the digital representation of cultural heritage within the context of visual communication design. The primary objective is to explore how text-to-image AI tools interpret and reproduce cultural motifs, symbols, and aesthetic elements. The methodology involved selecting specific motifs from Anatolian cultural heritage and generating visual outputs using different generative AI platforms, including Midjourney, DALL-E, and Stable Diffusion, based on various text prompts. The resulting images were analyzed through content analysis, focusing on fundamental design principles such as color, composition, texture, form, and symbolic meaning. Findings indicate that while generative AI tools offer creative diversity in cultural reinterpretation, they also exhibit contextual limitations in accurately preserving heritage references. The outcomes of the study provide recommendations for ethical, aesthetic, and technical approaches to cultural heritage representation in visual communication design. Future research may focus on strategies for safeguarding cultural heritage and developing sustainable models for its digital representation through generative AI.